Do personality traits influence the neural and cognitive response to emotion? - Martin, Rachael Marie (University of Essex, 2013)
Research shows that our personalities determine how we think, feel and behave. The aim of this research therefore was to examine individual differences in emotional responses on the basis of participants' scores for state-anxiety and the traits of anxiety, neuroticism and extraversion. Behavioural reaction times and neurological (EEG) were measured to emotional stimuli using dot-probe tasks. Further aims were to establish whether any differences found could be modulated by attentional training and to assess the use of alpha asymmetry in anxiety research. We found that trait-anxiety was the only trait to underpin differences in the response to emotion both behaviourally and neurologically. Although neuroticism and extraversion were responsible for differences in the response to emotion behaviourally they were not in the response to emotion neurologically. Our attentional training protocol had no effect on brain activity and a number of explanations are offered for this. When assessing the use of alpha asymmetry in anxiety research, differences based on trait-anxiety were evident supporting its use as a potential endophenotype for anxiety. We argue therefore that the most reliable measure of susceptibility and resilience to emotional disorders is an individual's level of trait-anxiety, both the cognitive and neurological response to emotional stimuli being evidently different dependent on an individual's score; this score also underlying differences in alpha asymmetry. Whilst evidence also indicates that differences in neuroticism and extraversion underlie individual differences in the cognitive response to emotion, this was not apparent neurologically suggesting that trait-anxiety is a more robust measure of susceptibility or resilience to emotional disorders and should therefore remain the focus of future research.